COMPARING ACCOUNTING CONCEPTS IN OVERVIEW OF ISLAMIC SCHOLAR'S: - cici dewi sari murni lezmantuleri (Jurisprudensi : Jurnal Ilmu Syariah, Perundangan-Undangan dan Ekonomi Islam, 2021)
This study aims to determine the accounting concept in Surah Al Baqarah verse 282 in the commentator's review. This research is qualitative through primary and secondary data sources with data analysis techniques using thematic methods. The findings of this study are the accounting concepts contained in the Qur'an are all human actions that cannot be separated from the values of divinity, humanity, prioritizing the public good, equal rights and obligations, and prohibiting cheating and immoral behavior. This is stated in Surah Al Baqarah verse 282 which contains about accounts payable or non-cash transactions, the verse contains orders to make records and bring witnesses.